Precapture of CO2 and Hydrogenation into Methanol on Heterogenized Ruthenium and Amine‐Rich Catalytic Systems - Anthony E. Szego; Dr. Tamara L. Church; Dr. Zoltán Bacsik; Dr. Aleksander Jaworski; Dr. Latif Ullah; Prof. Dr. Niklas Hedin (ChemistryOpen, 2023)
Abstract A heterogenized alternative to the homogeneous precapture of CO2 with amines and subsequent hydrogenation to MeOH was developed using aminated silica and a Ru‐MACHOTM catalyst. Commercial mesoporous silica was modified with three different amino‐silane monomers and used as support for the Ru catalyst. These composites were studied by TEM and solid‐state NMR spectroscopy before and after the catalytic reaction. These catalytic reactions were conducted at 155 °C at a H2 and CO2 pressures of 75 and 2 bar, respectively, with the heterogeneous system (gas‐solid) being probed with gas‐phase infrared spectroscopy used to quantify the resulting products. High turnover number (TON) values were observed for the samples aminated with secondary amines.